Clinical researchAssessment of selected oxidative stress parameters in patients with Wilson’s disease - Świątkowska-Stodulska, Renata; Dejneka, Wojciech; Owczarzak, Anna; Drobińska-Jurowiecka, Anna; Kiszkis, Hanna; Wiśniewski, Piotr; Sworczak, Krzysztof (Archives of Medical Science, 2009)
Introduction: Wilson’s disease is a genetic disorder of copper transport resulting in copper accumulation in different organs and their toxic injury. The involvement of antioxidative agent in Wilson’s disease has not been fully explained so far. Aim of the study was assessment of antioxidative status in patients with Wilson’s disease. Material and methods: The study involved 20 patients (12 men, 8 women, mean age 39.9 years) with a confirmed diagnosis of Wilson’s disease and 20 healthy volunteers representing the control group. During the study, the patients were in disease remission. Only in the patients with neurological form of Wilson’s disease some clinical symptoms persisted, although they were much less prominent. In the examined subjects, total serum antioxidative status was assessed by using colorimetric method, whereas glutathione peroxidase and superoxide dysmutase activities were assessed spectrophotometrically. The selenium concentration in the erythrocytes was examined by the atomic absorption spectroscopy. Additionally, in all the patients, biochemical parameters of liver injury and copper metabolism were assessed. Results: Markedly higher activity of the tested enzymes, total serum antioxidative status and erythrocytes selenium concentration were found in the patients when compared to the control group. While assessing the relationship between the analyzed parameters and copper metabolism indicators, a positive correlation between total serum antioxidative status, glutathione peroxidase activity, and 24-h urinary copper excretion was established. Conclusions: Higher erythrocyte activities of the antioxidative enzymes and total serum antioxidative status in patients with Wilson’s disease confirm activation of the antioxidative system in this group of patients.